Approximation method for the relaxed covariant form of the gravitational field equations for particles - Gallo, Emanuel (2012)
We present a study of the so called relaxed field equations of general relativity in terms of a decomposition of the metric; which is designed to deal with the notion of particles. Several known results are generalized to a coordinate free covariant discussion. We apply our techniques to the study of a particle up to second order.